Stvaranje hidrata i njihov utjecaj na unutrašnju koroziju cjevovoda prirodnog plina - Hydrate formation and its influence on natural gas pipeline internal corrosion - Obanijesu, E.; Pareek, V.; Gubner, Rolf; Tade, M. (Hrvatski nacionalni komitet svjetskog vijeca za naftu i plin, HAZU-Znanstveno vijece za naftu, 2011)
This study establishes the ability of hydrate formation to initiate internal corrosions along natural gas pipelines. The identified corrosion types, which are cavitations, erosion and corrosions by chemical reactions, are capable to individually or collectively initiate pitting and stress cracking corrosions which are also dangerous to gas pipelines. The impacts of these corrosion types are classified to economics, environmental and human loss with the economic loss as much as US$3 trillion depending on the pipe-length, location, sea depth, wave function, climatic conditions and political situations. Various predictive measures to minimize hydrate formations are finally recommended.